Os bolivianos e uma nova territorialidade na metrópole: o bairro do Brás - Losco, Luiza Nogueira [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The flux of Bolivian migrants to the city of São Paulo had its beginning in the 1950 decade, following bilateral agreements between Brazil and Bolivia, and was intensified since the beginning of 1980 decade, when existed a necessity of manpower in the textile sector of the city. The migratory fluxes previously stemmed of the North and Northeast regions of the country become less intense, having then the entrance of migrants coming from neighboring countries, the so called South Cone. The Bolivians leave their country in the search for better life conditions and find in São Paulo the possibility to insert them in the biggest concentration of financial capital in the Latin America. The objective of this research is to analyze the arrival of the Bolivian migrants to the city, having its locus of analysis the Brás region and the reflection about the foreigners that influenced the modification of the structure, both territorial and cultural, of the district and how is the relation between the Bolivians and the habitants previously established there

O fluxo de migrantes bolivianos para a cidade de São Paulo teve seu início na década de 1950, a partir de acordos bilateriais entre Brasil/Bolívia, e foi se intensificando a partir da década de 1980, quando existia uma necessidade de preenchimento de mão-de-obra no setor têxtil paulistano. Os fluxos migratórios anteriormente provindos das regiões Norte e Nordeste do país ficam menos intensos e tem-se a entrada de migrantes vindos de países vizinhos, os do chamado Cone Sul. Os bolivianos que saem de seu país buscam melhores condições de vida e encontram em São Paulo a possibilidade de se inserir na maior concentração do capital financeiro da América Latina. Esta pesquisa tem como objetivo analisar a chegada dos imigrantes bolivianos ao município, tendo como locus de análise a região do Brás e a reflexão acerca dos estrangeiros que influenciaram a modificação da estrutura, tanto territorial como cultural, do bairro paulistano e como se dá a relação entre bolivianos e os habitantes anteriormente ali estabelecidos
Keywords: Migração; Bolivianos; Territorialidade humana; Sociabilidade; Relações humanas; São Paulo (SP); Brás (São Paulo, SP)